Perbedaan Tingkat Kelekatan dan Kemandirian Mahasiswa Ditinjau dari Jenis Kelamin - Nur Hasmalawati; Nida Hasanati (State Islamic University (UIN) Ar-Raniry, 2018)
This study aims to determine the differences in attachment and self-direction in students. Subjects in this study were male and female students totaling 60 people, consisting of 30 men and 30 women whose ages ranged from 19-24 years. This study uses a different test analysis. Data collection techniques using a Likert Scale. The results of the analysis show that there is a a difference between the level of attachment and self direction in men and women. This is seen from the value of t= 0.2714 and sig 0.0009 < 0.05 which indicates that there are differences in the level of attachment of men and women. Likewise with self-direction, the results of the analysis indicate that there are differences in the level of self-direction of men and women seen from the value of t= 0.2794 and sig. 0.007< 0.05.